2021
DOI: 10.1128/jcm.00921-21
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of the L452R Mutation in the ACE2-Binding Interface of Spike Protein Triggers Recent Massive Expansion of SARS-CoV-2 Variants

Abstract: We report that there is a recent global expansion of numerous independent SARS-CoV-2 variants with mutation L452R in the receptor-binding domain (RBD) of the Spike protein. The massive emergence of L452R variants was first linked to lineage B.1.427/B.1.429 (clade 21C) that has been spreading in California since November-December 2020, originally named CAL.20C and currently variant of interest Epsilon. By PCR amplification and Sanger sequencing of a 541 base fragments coding for amino acids 414-583 of RBD from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
97
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(98 citation statements)
references
References 20 publications
1
97
0
Order By: Relevance
“…The alpha, gamma, delta and kappa variants of SARS-CoV-2 have N501Y, N501Y plus E484K, L452R, L452R plus E484Q mutations, respectively, in the viral Spike proteins [8][9][10]20,21]. These amino acid substitutions may be associated with the high contagiousness and/or immune escape of the variants [20,21]. We previously showed that TFDG may bind to the receptor binding domain (RBD) of the Spike proteins [7].…”
Section: Discussionmentioning
confidence: 99%
“…The alpha, gamma, delta and kappa variants of SARS-CoV-2 have N501Y, N501Y plus E484K, L452R, L452R plus E484Q mutations, respectively, in the viral Spike proteins [8][9][10]20,21]. These amino acid substitutions may be associated with the high contagiousness and/or immune escape of the variants [20,21]. We previously showed that TFDG may bind to the receptor binding domain (RBD) of the Spike proteins [7].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that some mutations have been acquired by different independent lineages in separate countries suggests there is a strong positive selection and possibly reflects an adaptive evolution of the virus in response to either the epidemiological control measures or a growing immunity to the original viral variants. Positive selection could therefore favor increased transmissibility, infectivity and/or immune escape of the virus [29].…”
Section: Discussionmentioning
confidence: 99%
“…Residue L452 is positioned at the edge of the binding interface with ACE2 and although this residue does not make direct contact with ACE2 [34,77], evidence suggests that substitution L452R enhances viral infectivity significantly [77,78]. Furthermore, it has been suggested that the L452R mutation is responsible for the dramatic clonal expansion of lineages carrying this mutation [79], possibly due to a decrease in the potency of antibody neutralization or through other immune escape characteristics [44,46,64,77,78,80]. Whether or not an effect of the L452R substitution on ACE2 binding, apparently modest, is a contributing factor in the rapid spread of variants carrying this mutation remains to be determined.…”
Section: Discussionmentioning
confidence: 99%